Experimental evidence for a severe proarrhythmic potential of levosimendan. (1st February 2017) - Frommeyer, Gerrit; Kohnke, Anja; Ellermann, Christian; Dechering, Dirk G.; Kochhäuser, Simon; Pott, Christian; Fehr, Michael; Eckardt, Lars
Abstract: Background: The calcium sensitizer levosimendan is established for therapy of acutely decompensated congestive heart failure. Clinical experience suggests a possible proarrhythmic potential. The aim of the present study was to assess possible proarrhythmic effects and underlying electrophysiological mechanisms. Methods and results: Ten rabbit hearts were isolated and Langendorff-perfused. Thereafter, levosimendan was infused in 3 concentrations (0.5, 1, and 2 μM). Eight endo - and epicardial monophasic action potentials and a 12-lead ECG showed a dose-dependent reduction of QT interval (0.5 μM: − 27 ms, 1 μM:-33 ms, 2 μM: − 77 ms; p < 0.05) and action potential duration at 90% of repolarization (APD90 ; 0.5 μM: − 12 ms, 1 μM: − 12 ms, 2 μM: − 20 ms). There was no significant increase in dispersion of repolarization. The described abbreviation of myocardial repolarization was accompanied by a significant decrease of effective refractory period (ERP; 0.5 μM: − 16 ms, 1 μM: − 20 ms, 2 μM: − 27 ms; p < 0.05). Under baseline conditions, ventricular fibrillation was inducible by programmed stimulation and aggressive burst stimulation in 3 of 10 hearts (4 episodes). After application of 1 μM levosimendan, 8 of 10 control hearts were inducible (27 episodes). Of note, in 8 of 10 hearts after infusion of up to 2 μM levosimendan, incessant ventricular fibrillation that could not be terminated by multiple external defibrillations occurred. Conclusion: In the present study, acute infusion of levosimendan resulted in an abbreviation of ventricular repolarization and a reduction of ERP. This led to a significantly elevated inducibility of ventricular fibrillation. In 8 of 10 hearts, incessant ventricular fibrillation occurred. These results suggest a proarrhythmic effect of levosimendan and might explain an increased mortality that coincided levosimendan treatment in a few small clinical studies.